Sustainability discourse in participatory planning: the case of Malaysia - Marlyana Azyyati Marzukhi (International Journal of Urban Sustainable Development, 2020)
The uprising of protests around the world in recent years, with protesters retaking the streets and demanding their voices be heard, has highlighted democracy’s disappearance. The crux of this argument centres on the process of governing, seemingly geared at ensuring market values are the only ‘sensible’ logic in planning processes. This study assesses whether the deployment of a transcendental ideal of planning discourse – sustainability – can be directed towards achieving capital accumulation through the transformations of governance practice. In this context, a case study in Malaysia is presented to demonstrate the complex ways in which the social order is regulated, as to what extent and through what processes participation matters in the planning process. The data were drawn from in-depth interviews with planners, members of parliament, local councillors,developers and non-government organisations.The findings highlighted the tensions between competing actors in the planning system and emphasised the imbalance of power under which the public have few options to resist.